2018
DOI: 10.3390/polym10050543
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and Nonisothermal Crystallization Kinetics of Poly(ε-caprolactone) Blended with a Novel Ionic Liquid, 1-Ethyl-3-propylimidazolium Bis(trifluoromethanesulfonyl)imide

Abstract: Recently, ionic liquids (ILs) and biodegradable polymers have become crucial functional materials in green sustainable science and technology. In this study, we investigated the influence of a novel IL, 1-ethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide ([EPrI][TFSI]), on the crystallization kinetics of a widely studied biodegradable polymer, poly(ε-caprolactone) (PCL). To obtain a comprehensive understanding, both the isothermal and nonisothermal crystallization kinetics of the PCL blends were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…For PCL, the Avrami indices are all above 2.5, which can be rounded to 3, revealing an instantaneous tridimensional (spherulitic) growth. In the literature, the n value for neat PCL is mainly reported to be between 2 and 3, but some researchers reported between 3 and 4. On the other hand, for PCL/AA blends, the Avrami exponents are averaging 2, hinting at instantaneous axialites rather than spherulites. Similar behavior has been reported for PCL composites. ,, …”
Section: Resultsmentioning
confidence: 99%
“…For PCL, the Avrami indices are all above 2.5, which can be rounded to 3, revealing an instantaneous tridimensional (spherulitic) growth. In the literature, the n value for neat PCL is mainly reported to be between 2 and 3, but some researchers reported between 3 and 4. On the other hand, for PCL/AA blends, the Avrami exponents are averaging 2, hinting at instantaneous axialites rather than spherulites. Similar behavior has been reported for PCL composites. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The nonisothermal crystallization parameters can be calculated by the fitting results of the Mo model. In general, the F ( T ) value of the Mo model can be correlated with the rate of nonisothermal crystallization. , A smaller F ( T ) value indicates a faster rate of nonisothermal crystallization. By the fitting results, we found that as the GO content in the composite increased, the F ( T ) values became smaller.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylene biocomposites for 3D printing, as well as biocomposites of lignocellulosic biomass and recycled PET, are prepared and characterized [32,33]. Biodegradable poly(ε-caprolactone) blends with ionic liquid are studied in regard to their crystallization characteristics [34]. Furthermore, the use of a green binder based on enzymatically polymerized eucalypt kraft lignin for fiberboard applications is tested [35].…”
Section: Contents Of This Issuementioning
confidence: 99%